Remembering American Journalist Michael Hastings (January 28 1980 – June 18 2013) [2021] - L (Intel Today, 2021)
“The CIA was also looking at infecting the vehicle control systems used by modern cars and trucks. The purpose of such control is not specified, but it would permit the CIA to engage in nearly unde…